A novel near-infrared styryl-BODIPY fluorescent probe for discrimination of GSH and its application in living cells. (May 2018) - Wang, Chengjun; Xia, Xiang; Luo, Jirong; Qian, Ying
Abstract: A novel near-infrared (NIR) fluorescent probe BODIPY-ONs for sensitive and selective detection of glutathione (GSH) was reported. The probe carried with 2, 4-dinitrobenzenesulfonyl group (DNBS) as quenching group was non-fluorescent. Upon addition of glutathione, an obvious NIR fluorescence recovery centered at 656 nm was observed and the quantum yield increased to 0.48, while other thiol-lacking amino acids did not generate any change. Compared with Cys and Hcy, BODIPY-ONs showed the highest response toward GSH. The limit of detection (LOD) for GSH was calculated as 131 nM from the titration experiments. The cleavage of the suphonate induced by GSH was proposed, which was supported by Mass spectral analysis and HPLC analysis. Further theoretical calculation indicated that an intermolecular hydrogen bond assited thiolysis process was the reason that BODIPY-ONs can discriminate GSH from Cys and Hcy. Moreover, probe BODIPY-ONs could also be used for endogenous and exogenous GSH detection in living cells. Graphical abstract: In this article, a novel GSH-selctive probe BODIPY-ONs based on the mechanism of intermolecular hydrogen bond assisted thiolysis was developed and applied to the detection of endogenous and exogenous GSH. Highlights: A novel near-inrared fluorescent probe BODIPY-ONs was synthesized. The probe BODIPY-ONs can discriminate GSH from Cys and Hcy. A new recognizing mechanism of intermolecular hydrogen bond assisted thiolysis was proposed. The probe BODIPY-ONs can apply to the detection of endogenous and exogenous GSH.